Preliminary studies on predatory potential of Australian ladybird beetle, Cryptolaemus montrouzieri Mulsant against Mealybug, Planococcus lilacinus Cockerell - Karthikeyan, A.; Lavanya, G.; Naveena, K.; Mangayarkarasi, P. (Recent Research in Science and Technology, 2022)
Mealybug Planococcus lilacinus Cockerell (Hemiptera: Pseudococcidae) damages Cocoa, Guava, Citrus, Cotton and other plant families. Besides causing direct loss to the plants they also reduce the market value of infested fruits. The extent of the damage may go up to 70 percent in a severe infestation. An Australian ladybird beetle, Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) introduced from Australia is a potential bio-control agent and is being utilized on many crops in Southern India. Mealybugs or scale insects constitute the natural food of certain ladybird beetles. The adult beetles as well as their larvae (grubs) seek the pests and feed voraciously on all stages. They often wipe out the entire pest colonies. The ladybird beetles are being used for suppression of mealy bugs in citrus, coffee, grapes, guava, ornamental and a variety of other crops. The feeding potential of different development stages of C. montrouzieri, a biological control agent against mealybugs, was investigated on P. lilacinus. Fourth instar grubs and adults of C. montrouzieri were the most voracious feeders of mealybug. The number of mealybug consumed by 1st, 2nd, 3rd and 4th instar larvae and adult beetles of C. montrouzieri was 20, 33.30, 37.50, 40 and 66.60 percent respectively. The results indicate that C. montrouzieri has the potential to be exploited as a bio-control agent. Inoculative releases of 4th instar larvae and adults may provide instant control of P. lilacinus. Field experiments should be conducted to determine the efficiency of the ladybird beetle on this mealybug.